BULANG (WOMEN’S HEAD COVERING) SIMALUNGUN BATAK ETHNIC - ramlan damanik; warisman sinaga; asriaty r purba; jekmen sinulingga; herlina (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
This article was written to reveal the meaning of the head covering for women or bulang for the Simalungun Batak community. The use of bulang or head coverings for women and what the meaning and function are for millennials, especially those who live in urban areas, has very little understanding. Therefore, the author created this article for describing the types of bulang and what the function and meaning of bulang are for the Simalungun Batak ethnic community. This research uses a qualitative approach and descriptive method and uses semiotic theory by Charles Sanders Pierce and data collection is carried out by observation, interviews and literature study. Data analysis was carried out using data reduction, translation and conclusions and suggestions. There are 4 types of bulang, namely Bulang Sulappei, Bulang Teget, Bulang Suyuk /Gijang and Bulang Hurbu Salalu. Bulang is for head cover and for giving identity. The meaning of wearing this bulang is as a symbol of maturity for Simalungun women.